Pelatihan Digital Marketing Pada Pelaku UMKM Sociopreneur Batik Kebon Indah Klaten - Nurhajati, Diani; Gunawan, Hamzah; Susanto, Djaelani; Aliami, Sri (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Batik Kebon Indah is the name of a batik business managed by some villagers in Kebon village, Bayat sub-district, Klaten Regency, Central Java. This batik business is managed by one of the village residents involving 15 batik craftsmen. Soiciopreuner's main products are handmade batik and printed batik in cloth form. During and after the Covid 19 pandemic, sales of Kebon Indah batik stopped, because the main consumers were foreign tourists who came directly to the production location to see the batik making process. Another problem that occurs is that Sociopreneur members are mothers/women who rarely use social media which can actually be used to promote their products anywhere. For this reason, the service team provides training which objective of this community service is to train the members of Sociopreuner Batik Kebon Indah to make use of social media platforms to promote their products. The results of the training show the enthusiasm of the training participants, it is proven that several training participants have started to promote their products regularly through social media: Instagram, Facebook and TikTok. The followers and viewers visiting the training participants' social media increased. By increasing the number of followers and viewers on the platform, it is hoped that it can increase product sales and increase guest visits to the batik product show room.